An empirical assessment of Leadership styles influences job satisfaction among hotel workers. In New Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The manner in which management demonstrates leadership may play a significant role in the character of the connection with the workforce as well as the level of cooperation and cohesion that exists. Therefore, the use of an appropriate leadership style and the employment of managers with strong leadership abilities can enhance an organisation as a whole. In order for executives to effectively achieve organisational goals, they must consider employees' job satisfaction, their performance, and their commitment to the organisation. This research project seeks to investigate and evaluate the significance of leadership qualities within the context of the Indian construction industry. The findings of this study can be used to formulate suggestions for the effective implementation of leadership skills in the hospitality industry.